Ultra-Wideband Fractal Ring Antenna for Biomedical Applications - Ilyas Saleem; Umair Rafique; Shobit Agarwal; Hüseyin Şerif SAVCI; Syed Muzahir Abbas; Subhas Mukhopadhyay (International Journal of Antennas and Propagation)
In this paper, an efficient, coplanar waveguide (CPW)-fed printed circular ring fractal ultra-wideband (UWB) antenna is presented for biomedical applications. In UWB technology, short-range wireless communication is possible with low transceiving power, a characteristic that is particularly advantageous in the context of microwave and millimeter-wave (mmWave) medical imaging. In the proposed antenna configuration, the UWB response is achieved by introducing wedged slots in the radiating patch, designed on a low-loss substrate. A CPW partial ground plane is truncated from the edges to optimize the antenna impedance. Experimental results indicate the antenna’s robust performance across the frequency range of 3.2–20 GHz. The well-matched measured and simulated results confirm our contribution’s employability. Furthermore, a time-domain study offers valuable insights into how the antenna responds to transient signals, highlighting its responsiveness and adaptability to biomedical applications.